Short-term effects of ambient air pollution on chronic obstructive pulmonary disease admissions in Beijing, China (2013–2017) - Gao N; Li C; Ji J; Yang Y; Wang S; Tian X; Xu KF (International Journal of COPD, 2019)
Nannan Gao,1 Chunhou Li,2 Jiadong Ji,3 Yanli Yang,1 Shaoting Wang,1 Xinlun Tian,1 Kai-Feng Xu1 1Department of Respiratory and Critical Care Medicine, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, China; 2Office of Medical Insurance, Peking Union Medical College Hospital, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, China; 3School of Statistics, Shandong University of Finance and Economics, Jinan, China Purpose: Evidence between air pollution and COPD admissions is inconsistent and limited in China. In this study, we aimed to explore the effects of air pollutants on COPD admissions in Beijing, China.Patients and methods: Daily COPD hospital admission visits derived from tertiary and secondary hospitals in Beijing were retrieved from January 2013 to February 2017. Air pollutant levels and meteorological data over the same periods were also achieved. Generalized additive model was applied to estimate the percentage changes with 95% CIs in daily admissions corresponding to 10 µg/m3 increases in pollutants levels [1 mg/m3 in carbon monoxide (CO)], stratified by age, gender, and season.Results: Seventy-three thousand seventy-six COPD hospital admission visits were included with mean daily visits of 48 (21). Cumulative lag effect with per 10 µg/m3 increase in air pollutant levels was largest for nitrogen dioxide (NO2) with 3.03% (95% CI: 1.82%–4.26%) at lag 06, for sulfur dioxide (SO2) with 2.07% (95% CI: 1.00%–3.15%) at lag 01, for particulate matter ≤10 µm in aerodynamic diameter (PM10) with 0.92% (95% CI: 0.55%–1.30%) at lag 07, and for particulate matter ≤2.5 µm in aerodynamic diameter (PM2.5) with 0.82% (95% CI: 0.38%–1.26%) at lag 06, respectively. Percentage increase for each 1 mg/m3 increase in CO was 5.99% (95% CI: 2.74%–9.34%) at lag 06. Further, stronger effects on COPD admissions were found in warm seasons than in cold seasons.Conclusion: Short-term exposures to PM2.5, PM10, NO2, SO2, and CO had adverse effects on COPD hospitalizations in Beijing with different magnitudes and lag days. Keywords: adverse effects, air pollution, COPD, time series analysis, hospital visits